Marriage market responses in the wake of a natural disaster in India - Shreyasee Das; Shatanjaya Dasgupta (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper examines the impact of the 2001 Gujarat earthquake on age at marriage and other assortative matching outcomes. Using the 2004-05 wave of the India Human Development Survey and employing a difference-in-differences strategy, we document that the earthquake reduced the age at marriage for both men and women and decreased the likelihood of women marrying into wealthier households. Additionally, we find no changes in matching by educational status or in the likelihood of intra-caste and out-of-village marriages. The results are driven by districts that were severely affected by the earthquake in terms of deaths and destruction. Our conjecture is that the negative economic shock pushed parents to marry off their daughters early to save on dowry expenditures. We confirm this underlying mechanism by using a proxy for dowry payments. Our results highlight how the institution of marriage can induce long-lasting demographic changes after a natural disaster.
Keywords: J12; J16; O53; 330; marriage; India; Gujarat earthquake; natural disasters; dowry